Impact of cataract surgery on driving difficulty and quality of life for older drivers - Fraser, Michelle Louise (Curtin University, 2011)
The demand for cataract surgery is set to increase due to the ageing population of Australia. Cataracts are usually bilateral, but cataract surgery is almost always performed one eye at a time. Previous investigations of the impact of cataract surgery seldom analysed the separate effects of each surgery. Instead, patients who underwent first, second or both eye surgeries were combined in the analyses. In Western Australia, public hospital patients wait substantial periods of time between first and second eye cataract surgeries. For these patients, understanding the separate effects of first eye surgery on driving difficulty, vision-related quality of life and depressive symptoms is of considerable importance for their safety and well-being.This before and after study aimed to gain a better understanding of the impact of first eye cataract surgery on self-reported driving difficulty, vision-related quality of life and depressive symptoms for older drivers. It also aimed to investigate how changes in these outcomes were associated with changes in objective visual measures after cataract surgery.The sample consisted of 99 bilateral cataract patients who drove and were about to undergo first eye cataract surgery. Participants were recruited consecutively from the Ophthalmology Departments of Royal Perth, Sir Charles Gairdner and Fremantle Hospitals in Perth, Western Australia. Participants were assessed during the week before and approximately 12 weeks after first eye cataract surgery. Data on major study outcomes including self-reported driving difficulty, vision-related quality of life and depressive symptoms, were collected using previously developed questionnaires, administered by the researcher. Three objective visual measures, namely visual acuity, contrast sensitivity and stereopsis, and two cognitive tests, namely the Mini Mental State Examination and a useful field of view test, were also conducted. In addition, demographic and health information were collected from participants.Separate generalised linear estimating equations were used to ascertain the changes in driving difficulty, vision-related quality of life and depressive symptoms after first eye surgery. Multiple linear regression modelling was then undertaken to determine whether changes in the major outcomes after surgery were associated with changes in objective visual measures.After first eye cataract surgery, there were significant mean improvements of approximately 10 points in overall driving difficulty (p<0.001) and vision-related quality of life (p<0.001) scores. There was a statistically significant but not clinically meaningful improvement in depressive symptoms of approximately one point after surgery (p=0.024). Before first eye surgery, 18% of participants did not meet the visual standards for licensing in Western Australia. After surgery this proportion was reduced to 4%.After controlling for confounding factors, change in surgery eye contrast sensitivity was the only objective visual measure significantly associated with change in driving difficulty after first eye cataract surgery (p<0.001). Change in surgery eye contrast sensitivity was also the only visual measure associated with change in vision-related quality of life (p<0.001). Stereopsis was the only visual measure associated with change in depressive symptoms after first eye surgery (p<0.032). Only 22% of participants received new glasses after first eye cataract surgery. Receiving new glasses after surgery was significantly associated with greater improvement in driving difficulty (p<0.001), vision-related quality of life (p<0.001) and depressive symptoms (p=0.001).Despite overall improvements, some participants did not improve or even declined in driving difficulty (19%), vision-related quality of life (14%) or depressive symptoms (47%) after first eye cataract surgery. For all three of the major outcomes, those who did not improve experienced significant improvements in surgery eye visual acuity and surgery eye contrast sensitivity after surgery, but not in stereopsis.Results found that first eye cataract surgery had significant benefits in terms of driving difficulty, vision-related quality of life and maintenance of levels of vision required for driver licensing, but not depressive symptoms. This provides strong grounds for Ophthalmologists to recommend cataract surgery to all suitable drivers with bilateral cataract, and for funding to be increased to reduce the waiting period for cataract surgery for public patients. Contrast sensitivity and/ or stereopsis, but not visual acuity, were associated with changes in the major outcomes after surgery. This challenges the current reliance on visual acuity for assessment and prioritisation of cataract patients for surgery, and in driver licensing. In addition, results suggest that the stereopsis measure may be useful for identifying bilateral cataract patients who do not improve after first eye cataract surgery, so they can be advised and possibly prioritised for second eye surgery.Further research is required to determine the additional effects of second eye cataract surgery for older drivers, to further uncover factors associated with non-improvement of cataract patients after first eye surgery and to develop appropriate visual tests for driver licensing.